“We Expressed What We Needed, and the Center Made changes…I Think They Listened:” Exploring Complexities of Participatory Action Research in Adult English for Speakers of Other Languages Program - Katherine Santos; Jana Sládková; Larissa Gaias; Johanna Tigert (Journal of Participatory Research Methods)
In this article, we discuss challenges and lessons learned from a Participatory Action Research (PAR) project conducted in collaboration between a public university and an adult education program focusing on adult English Speakers of Other Languages (ESOL). Over several months, university researchers regularly met with adult ESOL learners, who became researchers of their program to determine what works and what could be improved to serve them better. Simultaneously, a group of teachers engaged in an inquiry with one of the university researchers. We found PAR effective in engaging adult ESOL learners in changing their learning environment and simultaneously leading to improvement in their language skills. The project with teachers was not as successful as they saw their participation as an addition to their already busy work schedule. We ultimately found a need to ensure proper relationship building at the beginning of the project, balancing collaboration and autonomy of all participants, and navigating various time restraints when collaborating with adult ESOL learners on a PAR process.